Caderneta de saúde bucal materno-infantil: uma proposta para acompanhamento odontológico e para educação em saúde - Matos, Jaqueline Xavier (Universidade Federal do Tocantins, 2021)
The research presents a proposal for the construction of a child oral health booklet for dental follow-up in childcare and as an educational tool aimed at pregnant women and parents or caregivers of infants, involving dental informations analyzed in scientific literature documents and transformed into simple language, making accessible to evidence-based knowledge dissemination. From the point of view of its nature, it can be considered an applied research, for the purpose of producing material to be used in daily work practice. For its purpose, it is defined as methodological research, whose focus was the construction of an instrument that provides knowledge of specific subjects to the target audience, in addition to enabling records of dental follow-up. The construction of the booklet took place in stages: in the first, the subjects that would be part of the booklet were established, with indirect popular participation, and search strategies were developed for bibliographic research in the Pubmed, Virtual Health Library, Cochrane and Trip Database search interfaces. The selected articles are recent, from the last five years, represented by systematic reviews, with or without meta analysis, summaries of evidence and complemented by guides for clinical practice, for gathering and analyzing up-to-date knowledge, guiding protocols and offering conclusions scientifically reliable. In the next step, the information based on scientific evidence was adapted to simple language, in order to improve the understanding of the document's target audience. Next, photos were selected from a personal image bank, edited and mounted in the booklet, adding the texts and fields to record the infant's dental follow-up. The built oral health booklet seeks to contribute to dental surveillance, being a powerful support tool, by facilitating the comprehensive monitoring of maternal oral health during pregnancy, and infant, in the first two years of life. In addition, it is self-explanatory, didactic, easy to read and interpret, illustrated and can be used by health professionals and the general public after future validation steps, contributing to the dissemination of knowledge for self-care in health, both for pregnant women and for caregivers of newborns and infants.